An analysis of the Slovenian tax administration response during COVID-19 - Kovač, Polonca (Economic and business review, 2021)
Tax administration plays a key role in tax collection, striving for maximum public finance revenue, while at the same time protecting the rights of the taxpayers in tax procedures. The search for this balance is particularly relevant in times of crisis, as shown by the COVID-19 pandemic, especially in the first wave between March and June 2020. The article deals with the legal and economic aspects of work of the Financial Administration of the Republic of Slovenia (FARS) based on comparable data on tax measures in other countries, provided by international organizations such as IOTA and OECD, i.e. the EU. The article finds that in Slovenia the measures under consideration were often questionable already at the formal level, which led to a gap in the implementation of ‘intervention laws’ despite the relatively agile response by FARS. Nevertheless, it can be concluded that Slovenia’s public finance measures match the measures taken by other EU Member States. Also worth mentioning in such regard is that some of the measures, for example those regarding e-operation, were identified by both FARS and taxpayers as improvements to be preserved even after the pandemic, considering tax administration as a service for the state and taxpayers.
Keywords: COVID-19; davčna uprava; davčni postopki; Financial Administration of the Republic of Slovenia (FARS); Finančna Uprava Republike Slovenije (FURS); international comparison; intervencijski zakoni in ukrepi; intervention laws and measures; mednarodna primerjava; tax administration; tax procedure